Project-Based Learning for Improving Fourth-Grade Students’ Creative Thinking at SDN 060971 - Dyan Wulan Sari HS; Eka Kartika Silalahi (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Creative thinking is an important competence in elementary education because students need to generate ideas, use different strategies, create original responses, and elaborate their thinking in solving learning problems. In Natural and Social Sciences, creative thinking is particularly relevant because students are expected to observe phenomena, ask questions, design simple solutions, and connect scientific and social knowledge with daily life. This study investigated the improvement of fourth-grade students’ creative thinking skills through Project-Based Learning in Natural and Social Sciences at SDN 060971. The study employed a one-group pretest-posttest design involving 30 fourth-grade students. The main variable was students’ creative thinking skills, measured through four indicators: fluency, flexibility, originality, and elaboration. The score scale ranged from 0 to 100. Data were analyzed using descriptive statistics, N-Gain analysis, category distribution, and paired-sample t-test. The findings showed that students’ creative thinking skills improved from a pretest mean of 52.70 to a posttest mean of 77.25, with a mean gain of 24.55 points. The mean N-Gain was 0.52, which was categorized as moderate. The paired-sample t-test showed a statistically significant improvement, t(29) = 61.94, p < .001. Before the treatment, 24 students were categorized as less creative and 6 students were categorized as moderately creative. After the treatment, 29 students reached the creative category and only 1 student remained in the moderately creative category. Based on the indicator analysis, the highest improvement appeared in originality and flexibility, while fluency and elaboration also improved at a moderate level. The study concludes that Project-Based Learning can improve fourth-grade students’ creative thinking skills in Natural and Social Sciences, especially when students are guided to explore problems, design products, collaborate, present ideas, and reflect on their learning process.